Enhancing Security Protocols for MANETs in 5G-Enabled Smart Healthcare Systems - Alton Mabina (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
Mobile Ad Hoc Networks (MANETs) and 5G technologies offer transformative capabilities for healthcare systems, especially in developing countries like Botswana. MANETs provide decentralized, flexible connectivity, while 5G ensures high-speed, low-latency communication—together enabling critical services such as telemedicine, real-time patient monitoring, and emergency response. However, their integration introduces significant security risks, including data breaches, unauthorized access, and system vulnerabilities. This paper proposes a Comprehensive Multi-Layer Security Framework to address these challenges, combining encryption, secure MANET routing protocols, 5G network slicing, blockchain authentication, and AI-driven intrusion detection. The framework aims to secure patient data at every network layer, enhancing system integrity, confidentiality, and availability. Implementation strategies include phased infrastructure development, workforce training, and the creation of data protection regulations. The study also emphasizes the importance of international cooperation and technology adaptation for resource-constrained environments. By adopting this model, Botswana can establish a secure, scalable healthcare infrastructure that supports innovation and improves access to quality care.